The impact of economic freedom on foreign direct investment: a study of selected Southeast Asian economies - Buu Kiem Dang; Minh Duc Trinh (Journal of Economics and Development)
Purpose – This study investigates the impact of economic freedom and its components, including business freedom, trade freedom, investment freedom, financial freedom and monetary freedom, on foreign direct investment net inflows (FDI net inflows). Design/methodology/approach – The sample consists of six Southeast Asian countries, which are Cambodia, Indonesia, Malaysia, the Philippines, Vietnam and Thailand, covering the period from 1995 to 2022. The study employs various panel data estimation methods, including fixed-effects model (FEM), random-effects model (REM), generalized least squares (GLS) and the Driscoll–Kraay standard error method to operationalize our research objectives. Findings – The research results show that the economic freedom index has a positive impact on FDI net inflows. However, the effects of the subcomponents of economic freedom vary. In particular, trade freedom and financial freedom positively impact FDI net inflows, while monetary freedom has a negative relationship with FDI net inflows. Moreover, we find no evidence of a relationship between business freedom, investment freedom and FDI net inflows. Practical implications – The findings imply that Southeast Asian governments should consider further improving economic freedom, trade freedom and financial freedom policies to strategize for attracting FDI. Originality/value – This study is the first to explicitly examine the impact of economic freedom and its components, including business freedom, trade freedom, investment freedom, financial freedom and monetary freedom, on foreign direct investment net inflows in the context of Southeast Asian countries. This aspect has not been clearly addressed in previous research.